Chitosan coated-phosphorylated starch films: Water interaction, transparency and antibacterial properties - Merino, Danila (2018)
Since there is a current need for developing biodegradable mulch films that keep the advantages of those manufactured with polyethylene but offering earlier biodegradation, new starch-based formulations were proposed and analyzed. In this work, starch was chemically modified by phosphorylation with sodium tripolyphosphate and resulting films were later coated with chitosan. Starch phosphorylation was performed by two different methodologies: chemical modification in aqueous suspension (AS) and reactive extrusion (REx). The content of phosphorus and the degree of substitution (DS) were determined and calculated, respectively, for the purpose of evaluating the efficiency of the phosphorylation reaction. This was used as a reference to analyze its incidence on the structure of the materials tested. Fourier Transform infrared spectroscopy (FTIR) and X ray diffraction (XRD) techniques were used to analyze chemical and structural modifications of the starch. Results show that higher DS was achieved by REx method and that was supported by the analysis of FTIR and XRD spectra. Films characterization indicates that phosphorylation by REx contributed to lower film moisture content and to increase opacity and antimicrobial activity. With regard chitosan (CS) coating, SEM micrographs indicate that it presented a porous structure that produces an increment in hydrophilicity, opacity and antimicrobial activity.